Determination of Dipyrone in Pure Form and Pharmaceutical Formulations by Differential Pulse Polarographic Analysis - Aziz Ramadan, Abdul; Mandil, Hasna; Hafez, Baraa (Asian Journal of Chemistry, 2010)
Differential pulse polarographic analysis of dipyrone in phosphate buffer (0.002 M Na2HPO4·12H2O + H3PO4) at pH 3.5 was performed by using dropping mercury electrode, static mercury drop electrode and hanging mercury drop electrode. One oxidation peak was observed in the range -540 to -560 mV (Ep) and the peak current Ip is linear over the ranges 1.00-50.00 μM using dropping mercury electrode and 3.80-50.00 μM using static mercury drop electrode and hanging mercury drop electrode. differential pulse polarographic analysis has been used successfully for the determination of dipyrone in pure and pharmaceutical formulations. The relative standard deviation did not exceed 4.9, 4.2 and 4.5 % for the following concentrations of dipyrone: 1.00 μM using dropping mercury electrode and 3.80 μM using static mercury drop electrode and hanging mercury drop electrode, respectively.